Think Pair Share Berbantuan LKM Puzzle Meningkatkan Kolaborasi dan Keterampilan Membaca Puisi Siswa Kelas II - Fahrezy, Fiona Fazra; Purwati, Panca Dewi (YASIN, 2025)
Cooperative learning has been widely examined; however, studies that specifically integrate the Think Pair Share (TPS) model with LKM Puzzle to enhance collaboration and poetry reading skills among elementary school students remain limited. This study aims to describe the implementation and analyze the effectiveness of the TPS model assisted by LKM Puzzle in improving collaboration and poetry reading skills among second-grade students at SDN Krobokan. The study employed a descriptive quantitative approach with supporting qualitative data and a saturated sampling design involving 26 students. Data were collected through observation, poetry reading tests, and documentation, and were analyzed using descriptive statistics and N-Gain calculations. The findings show a significant improvement in poetry reading skills, indicated by an increase in the average score from 58 (pretest) to 82 (post-test) and an increase in mastery from 45% to 87%; an N-Gain score of 0.57 indicates a medium level of improvement. Students’ collaboration skills also improved, particularly in the aspects of sharing tasks and responsibilities, which reached the “very good” category for all students. These findings indicate that the TPS model assisted by LKM Puzzle is effective in increasing active engagement, collaboration, and poetry reading skills. The implications of this study include a theoretical contribution to the development of puzzle-based learning media and practical recommendations for teachers in implementing interactive and enjoyable learning strategies, while future research is encouraged to broaden the application context or employ experimental designs to strengthen the generalizability of the findings.